DAKWAH: SUATU PENDEKATAN KULTURAL - Muhammad Alim Ihsan (State Institute of Islamic Studies (IAIN) Palu, 2008)
Inviting people to perform the good deeds is one of the Islamic core teachings. For this reason, a da’wah should be delivered by employing a proper approach. In other words, a dâ’i should notice the social and cultural condition of the people as the target of his da’wah. Within this context, one of the approaches that can be employed in delivering a da’wah is cultural approach. Employing this kind of approach, a dâ’i will be able to promote the Islamic teaching as a social and cultural need of the Muslims. In addition, cultural approach is persuasive in nature, that is transforming the values of the Qur’an and the prophet’s tradition into ideas and deeds in the form of norms.Kata Kunci : dakwah, pendekatan kultural, penyebaran Islam